Unlimited Liability as a Barrier to Entry - Carr, Jack L.; Mathewson, G. Frank (Journal of Political Economy, 1988)
Many, but not all, firms have the freedom to choose liability rules. In some countries, service professions have unlimited liability rules imposed by government; historically, banks in some countries faced unlimited liability. Why do governments impose unlimited liability? This is the question the authors address. With a simple model, they illustrate the agency conflicts in firms. Limited liability solves these conflicts efficiently. Unlimited liability raises the cost of capital; inefficiently small firms result. But under some conditions, selectively-applied unlimited liability rules protect rents. The authors test several propositions with data on Scottish banking and U.S. law firms. Copyright 1988 by University of Chicago Press.